2022
DOI: 10.3389/fpsyt.2022.897002
|View full text |Cite
|
Sign up to set email alerts
|

Systematic review on somatization in a transcultural context among teenagers and young adults: Focus on the nosography blur

Abstract: AimsSomatic complaints are a frequent cause for consultation in primary care. In a transcultural context, somatic complaints are typically associated with psychological distress. A recent review about somatic symptom disorders in adolescence showed some nosographic heterogeneity and outlined various etiological hypotheses (traumatic, environmental, or neurologic), separate from the cross-cultural considerations. Migrants' children encounter specific problems involving cultural mixing-issues of filiation (famil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 97 publications
0
2
0
Order By: Relevance
“…Yet, expressing suffering and soma symptoms can vary depending on culture . In some cultures that stigmatize mental health problems, psychological symptoms are expressed in the form of physical complaints such as insomnia, fatigue, chest pain, or heart pain [14]. In the context of COVID-19 crisis, with its suddenness beyond human expectations, has increased not only anxiety disorders, depression, and suicidal thoughts, but also increased somatoform disorders.…”
Section: Definition Of Key Terms On Somatic Symptomsmentioning
confidence: 99%
See 1 more Smart Citation
“…Yet, expressing suffering and soma symptoms can vary depending on culture . In some cultures that stigmatize mental health problems, psychological symptoms are expressed in the form of physical complaints such as insomnia, fatigue, chest pain, or heart pain [14]. In the context of COVID-19 crisis, with its suddenness beyond human expectations, has increased not only anxiety disorders, depression, and suicidal thoughts, but also increased somatoform disorders.…”
Section: Definition Of Key Terms On Somatic Symptomsmentioning
confidence: 99%
“…Moreover, mental illness carries a great stigma in Vietnamese culture, and thus individuals will tend to somaticize their problems and report only the physical symptoms or less significant elements [5]. It has been reported that symptoms of tiredness or fatigue, loss of sleep, heart issues, stomachache were found in the survivors of COVID-19 epidemic and there would be 15 symptoms that the human body can reveal when faced with stressful experiences, specifically: 1) stomach pain; 2) back pain; 3) pain in arms, legs, and joints; 4) menstrual disorders, dysmenorrhea (for women); 5) headache; 6) chest pain; 7) dizziness/lightheadedness; 8) fainting; 9) heart palpitations; 10) difficulty breathing ; 11) difficulties in sex life; 12) constipation or diarrhea; 13) nausea, belching, indigestion; 14) fatigue, lack of strength; 15) difficulty sleeping (CDC, 2021; DSM-V). Researchers also stated that long COVID-19 syndrome shares similarities with somatic syndromes characterized by persistent somatic symptoms of unclear etiology [6].…”
Section: Introductionmentioning
confidence: 99%